The Theatre of Mind: An educational tool of teaching Emotional Intelligence via ICTs and distant learning - Gatsakou, Christina; Bardis, Nikolaos; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The aim of this paper is to provide a different approach in the educational process, introducing “The Theatre of Mind” - a term that we use instead of the term tabletop Role Playing Games (tRPGs)- as a powerful interdisciplinary educational tool with a view to cultivating and developing the emotional intelligence of students. According to this approach, my intention is to indicate how the use of the Theatre of Mind in the educational environment can be an integral asset; not only in teaching school’s subjects (ex. Language, History, Physics etc.) but also in teaching behavior, culture, ideals, and ethical values. Therefore, it aims at student’s mental and emotional stimulation targeting the integration of mental and emotional process emphasizing the latter. Thus, the Theatre of Mind may provoke and develop concrete emotions, manners and behavior through simulating real life. It is a method that may provide a unique experience for the student. Concluding, I suggest that the Theatre of Mind due to its nature and by means of a special design can function as the field where learners will deal with a holistic cultural experience monitoring and developing emotional intelligence even in distant learning.